Accessing higher education leadership: Towards a framework for women's professional development - Moodly, A.; Toni, N.M. (South African Journal of Higher Education, 2017)
Women’s academic pathways are not linear and chronological, requiring a well-thought model to deflect the accidental nature in which women seem to come into leadership positions. The gendered nature of Higher Education Institutions (HEIs) that emanates from the institutional culture and the perception of leadership in women as a culture of service has impacted negatively on women and leadership. A structured planned approach, can address the shortages of women representation and also address the gap identified in terms of the cultural and environmental contexts that create barriers. The authors present a theoretical overview based on literature and previous empirical research, and propagate that a model should be put in place towards a life-cycle continuum of professional development for women. Based on Huberman’s Teacher Life Cycles stages, it is particularly advanced to contend with factors as identified that impact on the dearth of women in HE leadership positions.